2005
DOI: 10.4319/lo.2005.50.3.0864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV‐B and different PAR intensities on the primary production of the mixotrophic planktonic ciliate Stentor araucanus

Abstract: Stentor araucanus is a mixotrophic ciliate that, in Andean lakes, inhabits the upper epilimnetic levels, which are commonly avoided by other planktonic organisms. This freshwater heterotrich has dark pigmented cortical granules and lives autotrophically with endosymbiotic algae. The effect of photosynthetically active radiation (PAR) and ultraviolet (UV)-B radiation on primary production was analyzed during summer [2003][2004] in Lake Moreno Oeste, a highly transparent ultraoligotrophic lake (mean summer K d ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
3
47
0
1
Order By: Relevance
“…In these lakes, mixotrophic flagellates and ciliates dominate the bacterivorous fraction though in low abundance (Modenutti and Balseiro 2002;Modenutti et al 2005Modenutti et al , 2008. Furthermore, all these lakes exhibit high C : P ratios in accordance with the light-nutrient hypothesis (Sterner et al 1997).…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…In these lakes, mixotrophic flagellates and ciliates dominate the bacterivorous fraction though in low abundance (Modenutti and Balseiro 2002;Modenutti et al 2005Modenutti et al , 2008. Furthermore, all these lakes exhibit high C : P ratios in accordance with the light-nutrient hypothesis (Sterner et al 1997).…”
mentioning
confidence: 65%
“…Another possibility would be that the ciliate O. naumanni, which increases its abundance toward the 1% PAR depth, decreases filament length at deeper layers of the euphotic zone by preying upon them. However, previous work showed that O. naumanni preys on particles ,1 mm (Modenutti and Balseiro 2002) and through catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH) dye analysis no filaments were observed in food vacuoles of this ciliate species . Therefore, the inverse relation between filament proportion and O. naumanni abundance was not the consequence of a top-down effect.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations